Urban and regional transportation modeling : essays in honor of David Boyce - Boyce, David E.; Lee, Der-Horng, 1967- (Cheltenham, UK ; Northhampton, Mass. : E. Elgar, 2004)
Honoring David Boyce for his legendary contributions to the fields of transportation modeling and regional science, the chapters in this festschrift highlight and analyze state-of-the-art and state-of-the-practice methodologies and theories in transportation modeling, regional and urban planning.
Includes bibliographical references and index.
oif 12/08/15
Loan
Keywords: Urban transportation -- Mathematical models; Urban transportation -- Planning; Regional planning